Advances in cell and molecular diagnostics - Raghavendra, Pongali; Pullaiah, T. (UK: Elsevier, Academic Press, 2018)
Advances in Cell and Molecular Diagnostics brings the scientific advances in the translation and validation of cellular and molecular discoveries in medicine into the clinical diagnostic setting. It enumerates the description and application of technological advances in the field of cellular and molecular diagnostic medicine, providing an overview of specialized fields, such as biomarker, genetic marker, screening, DNA-profiling, NGS, cytogenetics, transcriptome, cancer biomarkers, prostate specific antigen, and biomarker toxicologies. In addition, it presents novel discoveries and clinical pathologic correlations, including studies in oncology, infectious diseases, inherited diseases, predisposition to disease, and the description or polymorphisms linked to disease states. This book is a valuable resource for oncologists, practitioners and several members of the biomedical field who are interested in understanding how to apply cutting-edge technologies into diagnostics and healthcare.
Chapter 1. Cellular and Molecular Diagnostics: An Introduction -- Chapter 2. RNA-Based Applications in Diagnostic and Therapeutics for Cancer -- Chapter 3. Advancements in Genetic Applications for Cellular and Molecular Diagnostics -- Chapter 4. Biomedical Imaging Role in Cellular and Molecular Diagnostics -- Chapter 5. Breast Cancer-Targeted Therapy Using Nanocarriers -- Chapter 6. Human Papillomavirus- and Epstein- Barr Virus-Caused Tumor Diagnosis and Therapy -- Chapter 7. Pathogen Identification Using Novel Sequencing Methods -- Chapter 8. Future of Cellular and Molecular Diagnostics: Bench to Bedside.
Includes bibliographical references and index.
Keywords: Molecular diagnosis; Cells; Pathology, Molecular; Cytogenetic Analysis; Molecular Diagnostic Techniques; Molecular diagnosis; Pathology, Molecular